Solving delay differential equations of small and vanishing lag using multistep block method - Abdul Aziz, Nurul Huda; Abdul Majid, Zanariah; Ismail, Fudziah (Hindawi Publishing Corporation, 2014)
This paper considers the numerical solution of delay differential equations for solving the problem of small and vanishing lag using multistep block method. This problem arises when the size of a delay value is smaller than the step size, x - τ < h, and the delay time may even vanish when τ → 0 in a current step. The proposed approach that is based on interpolation of Newton divided difference has been implemented by adapting this problem to the multistep block method. In order to achieve the required accuracy, this approach considered the appropriate degree of interpolation polynomial in approximating the solution of delay term. The developed code for solving small and vanishing lag is done using C program and we called it as DDEB5. The P-stability and Q-stability of this method are also studied. Numerical results are presented and compared to the existing method in order to illustrate the efficiency of the proposed method.